METHODICAL APPROACHES TO MONITORING THE STABILITY OF THE BANKING SYSTEM OF UKRAINE IN THE CONTEXT OF FORMATION OF INVESTMENT RESOURCES OF POST-WAR RECOVERY - Filipov, Denis V. (Journal of Strategic Economic Research, 2025)
The article examines existing approaches to the concepts of "bank stability" and "bank financial stability" and defines their correlation. It is noted that the financial stability of banks, as a type of stability, is of great importance for the development of any economic relations. In the process of generalizing the methodological approach to monitoring the stability of the banking system, recommendations of international organizations are given, and it is noted that in practice, both individual indicators and cumbersome methods are used, which involve the calculation of dozens of indicators. Based on a review of leading scientists’ views, it was recommended to conduct a stability analysis at the macro level and at the levels of systemic and individual banks. The analysis of the stability of the banking system in Ukraine involves the use of the methodology recommended by the International Monetary Fund, and therefore is carried out in three stages: asset quality assessment, extrapolation of results, and stress testing. The impact of the war on monitoring the stability of the banking system was manifested in fragmented implementation: the analysis was not carried out every year, was not fully conducted (in terms of the analysis stages), and did not cover all banks. In the context of post-war recovery, it is important to monitor banks’ credit and investment activities. Among the main measures to improve monitoring of the stability of the banking system in wartime, it is proposed to analyze in detail the state of the financial market, the structure of loan and investment portfolios, the resource base of the banking sector, penetration of new markets for banking services, the structure of sources of financial resources, loan and investment portfolios, and the optimal ratio of banks’ equity and liabilities.